Prevalence of Sinew String in Patients Coming to a Tertiary Care Hospital: A Descriptive Cross-Sectional Study - Talha Tanveer, Bushra Jabeen, Syed Ahmed Omer, Sana Adeeba Islam, Humaira Naureen, Marium Azfar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The aim of this study to evaluate the dentulous and edentulous maxillae in the microstructure of the incisive canals and their surrounding bone in order to show the structural qualities. Study Design: The study was cross sectional being conducted at the Dental Department of DOW International Dental College, Karachi for six month from July 2022 to December 2022. Methodology: A total number of patients was N=240. The right and left sides of each patient were classified as either edentulous or dentulous. After receiving written consent, the patients who were monitored on both were checked to see if sinew string was present or not. The data was analyzed by SPSS 21. Results: There were 240 patients in all, 130 of whom were men and 110 of them were women. Males (54.1%) and females (46%) made up the edentulous and dentulous group. The patients with the greatest ages were 21- 51 years old. The patients’ average age was 38 ± 15 years. The sinew string frequency was similar with respect gender. There was significant difference between edentulous and dentulous; p<0.005** on both sides observed by using simply seen, pushing on the oblique line and pulling the cheek sideways. Conclusion: Sinew string was attempted to maintain and control buccal mucosa movement and block the mouths posterior vestibule. The occurrence of sinew strings was greater than usual. Keywords: Sinew strings, Dentulous, Edentulous, mandibular.